login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 59th year, we have over 358,000 sequences, and we’ve crossed 10,300 citations (which often say “discovered thanks to the OEIS”).

Other ways to Give
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A179200 E.g.f. equals the real part of the i-th iteration of (x + x^2), where i=sqrt(-1). 2
0, 1, 0, -6, 60, -600, 5880, -38640, -624960, 45077760, -1773129600, 58531809600, -1657462435200, 33703750080000, 171919752076800, -76383384045696000, 6034124486347776000, -348318907415331840000, 15862493882862941184000 (list; graph; refs; listen; history; text; internal format)
OFFSET

0,4

COMMENTS

Let H(x) equal the i-th iteration of (x + x^2), then

. the inverse of H(x) equals the conjugate of H(x);

. H(x+x^2) = H(x) + H(x)^2;

. H(x) = F(x) + i*G(x) where G(x) = e.g.f. of A179201 and F(x) = e.g.f. of this sequence, where H(F(x) - i*G(x)) = x;

. coefficients of H(x) form the first column of triangular matrix A030528 raised to the i-th power, where A030528(n,k) = C(k,n-k).

LINKS

Table of n, a(n) for n=0..18.

FORMULA

E.g.f.: F(x) satisfies:

. F(x) = (G(x+x^2)/G(x) - 1)/2

. G(x) = sqrt( F(x) + F(x)^2 - F(x+x^2) )

where G(x) is the e.g.f. of A179201.

EXAMPLE

E.g.f: F(x) = x - 6*x^3/3! + 60*x^4/4! - 600*x^5/5! + 5880*x^6/6! +...

The e.g.f. of A179201, G(x), begins:

G(x) = 2*x^2/2! - 6*x^3/3! + 12*x^4/4! + 200*x^5/5! - 6240*x^6/6! + 139440*x^7/7! - 2869440*x^8/8! +...

The i-th iteration of (x + x^2) = H(x) = F(x) + i*G(x), begins:

H(x) = x + i*x^2 - (1 + i)*x^3 + (5 + i)*x^4/2 - (15 - 5*i)*x^5/3 + (49 - 52*i)*x^6/6 - (23 - 83*i)*x^7/3 - (93 + 427*i)*x^8/6 + (15652 + 18537*i)*x^9/126 - (61567 + 24585*i)*x^10/126 + (369519 - 42094*i)*x^11/252 - (1743963 - 1222750*i)*x^12/504 + ...

where H(F(x) - i*G(x)) = x.

PROG

(PARI) {a(n)=local(M=matrix(n+1, n+1, r, c, if(r>=c, binomial(c, r-c))), L=sum(k=1, #M, -(M^0-M)^k/k), N=sum(k=0, #L, (I*L)^k/k!)); if(n<1, 0, real(n!*N[n, 1]))}

CROSSREFS

Cf. A179201, A030528.

Sequence in context: A122653 A299869 A136943 * A136938 A136930 A136936

Adjacent sequences: A179197 A179198 A179199 * A179201 A179202 A179203

KEYWORD

sign

AUTHOR

Paul D. Hanna, Jul 02 2010

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified December 9 23:05 EST 2022. Contains 358710 sequences. (Running on oeis4.)